1998
DOI: 10.1021/jo971826v
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic Synthesis of Lysophosphatidylnucleosides

Abstract: 5‘-O-Lysophosphatidylnucleosides [5‘-O-(1-O-acyl-sn-glycero-3-phosphoryl)nucleosides] were obtained by a two-step chemoenzymatic synthesis. 5‘-O-(sn-Glycero-3-phosphoryl)nucleosides (5‘-GPNs) were first prepared from a phosphoramidite of 1,2-O-isopropylidene-sn-glycerol and appropriately protected nucleosides, applying the phosphoramidite methodology on the solid phase or in solution. In a following step, the regioselective acylation at the C-1 hydroxyl of the glycerol moiety of 5‘-GPNs was achieved by a lipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…To achieve the preparation of 3′‐ O ‐lysophosphatidylnucleosides we planned to follow the same two‐step chemoenzymatic strategy as previously used for the preparation of 5′‐ O ‐lysophosphatidylnucleosides 1. Therefore, mono[(2 R )2,3‐dihydroxypropyl] esters of 3′‐nucleotides (3′‐GPNs) had to be prepared first, possibly with modification of the chemical step.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To achieve the preparation of 3′‐ O ‐lysophosphatidylnucleosides we planned to follow the same two‐step chemoenzymatic strategy as previously used for the preparation of 5′‐ O ‐lysophosphatidylnucleosides 1. Therefore, mono[(2 R )2,3‐dihydroxypropyl] esters of 3′‐nucleotides (3′‐GPNs) had to be prepared first, possibly with modification of the chemical step.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that various lipases (including Lipozyme) in organic solvents in the presence of substrates bearing different kinds of alcoholic functions preferentially acylate the primary ones 4,5. Thus, in the case of 5′‐GPdNs,1 bearing only one primary and two secondary hydroxyls, it had not been surprising to find that the enzyme had been able to acylate the primary hydroxyl of the glycerol moiety selectively. In 3′‐GPdNs there are two primary hydroxyls − both, in principle, susceptible to enzymatic acylation − present in the molecule, in addition to a secondary hydroxyl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acyclovir (9‐(2‐hydroxyethoxymethyl)guanine) is an acyclic nucleoside analogue that has shown a potent antiviral activity, and it is known to inhibit the replication of herpes viruses and hepatitis B virus 18–20. However, acyclovir has rather short plasma half‐life (about 2–3 h in adults without renal impairment) and limited selectivity 21, 22.…”
Section: Introductionmentioning
confidence: 99%